Plasticité de l’entropie urbaine - Hermange, Emmanuel (CV Photo, 2003)
Abstract Stéphane Couturier's Villes génériques series is a continuation of the photographic work on urban sites under construction that he has been producing for a number of years. This archaeology of historical strata of the city has a counterpoint in his photographs of buildings that have become the emblem of a modernity that extends its functional and utilitarian logic to all four corners of the earth. Images taken in Seoul, Moscow, and Beijing attempt to capture this proliferation, which relegates to second place local specificities, replacing them with generic ways of life and of living.